PERANCANGAN IKLAN LAYANAN MASYARAKATPENTINGNYA PENDIDIKAN ANAK DI USIA DINI - Habel Sutopo; Didiek Prasetya; Yayan Hariansyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Families Are A Institutions of the First and Main For A Child. Children in Families hearts feel the comfort and closeness that old orangutan will provide stimulation WITH Easy For A Child Development. Giving A Child Education showed to be started early age, BECAUSE IN Early Childhood Children will WITH EACH RECEIVE Easy Share stimulation Its impact his future later. Through advertising SERVICES 'public importance Child Education in Early Childhood The singer is expected kita ALL Both society and especially older orangutans can be involved in guiding the sons kita since Early For Smart Indonesia.Keywords: PSA, Kids, Family